Relationship between ecto-enzymatic activity and organic substrates availability (Ross Sea, Antarctica): an experimental approach - MISIC, CRISTINA; POVERO, PAOLO; FABIANO, MAURO (Springer Verlag Germany:Tiergartenstrasse 17, D 69121 Heidelberg Germany:011 49 6221 3450, EMAIL: g.braun@springer.de, INTERNET: http://www.springer.de, Fax: 011 49 6221 345229, 1998)
Organic matter consumption and decomposi- tion were studied in four experimental systems, having collected di erent organic substrates in the Ross Sea in December 1994. For the experimental approach selected, processes normally acting on a mixed pool of substances could be separated and the main features of each phe- nomenon could be focused on. Through the strict rela- tionship between each experimental system and natural conditions shown by organic matter assessment, ecto- enzymatic activity trends and their relation with Ant- arctic water substrates could be described. Through ice melting the water column becomes rich in large pools of substrates, as well as enzyme-producing micro-organ- isms, capable of quick development. The quantitative predominance of leucine-aminopeptidase throughout the year is well known, but its relative importance seems to decrease when, owing to production events, the en- vironment is enriched with autotrophic- and heterotro- phic-derived substances, leading to glycolytic enzymes expression. Thus, ectoenzymatic activity is supposed to be one of the factors responsible for organic matter variations, showing quantitative and qualitative changes depending on substrate availability.